Implementasi kebijakan sistem zonasi PPDB di SMPN 59 surabaya - Putri Purwati, Nikita; Holiso, Nur; Indah Sukmah, Nu'rani; Trihantoyo, Syunu; Nubhanudin, Nubhanudin (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
The zoning system policy is to improve the quality of education in all schools and to equalize the quality of education in each region. With this zoning system, we can see that there are no longer superior or favourite schools. All schools have good educational services to improve the quality of education in their schools. This research uses a type of descriptive research using a case study design because the information is obtained from the researchers direct presence in the field. The research results show that the PPDB zoning system at SMPN 59 Surabaya runs effectively and efficiently. They carry out this policy based on the system from the education office without making any changes at all. School principals have special strategies to improve the quality and quality education staff to accommodate all forms of student competency received. This zoning system creates equality between schools so that everything is the same and equal. The impact of implementing this policy includes increasing acces to education for people in remote or less developed areas, as well as reducing the level of competition to enter superior schools